Inflammation and Progression of Cholangiocarcinoma: Role of Angiogenic and Lymphangiogenic Mechanisms - Roy, Sukanya; Glaser, Shannon; Chakraborty, Sanjukta (Frontiers in Medicine, 2019)
Cholangiocarcinoma (CCA), or cancer of the biliary epithelium is a relatively rare but aggressive form of biliary duct cancer which has a 5-year survival rate post metastasis of 2%. Although a number of risk factors are established for CCA growth and progression, a careful evaluation of the existing literature on CCA reveals that an inflammatory environment near the biliary tree is the most common causal link between the risk factors and the development of CCA. The fact that inflammation predisposes affected individuals to CCA is further bolstered by multiple observations where the presence and maintenance of an inflammatory microenvironment at the site of the primary tumor plays a significant role in the development and metastasis of CCA. This review aims to address the role of an inflammatory microenvironment-CCA crosstalk and will present the basic concepts, observations and current perspectives from recent research studies in the field of tumor stroma of CCA.